Analysis of Land Suitability for Mangrove Ecotourism in Tanjung Lesung, Banten Province - Tahapary, Gifano Gias Gemayal; Riyantini, Indah; Pamungkas, Wahyuniar; Taofiqurohman, Ankiq (Graduate School, Universitas Brawijaya, 2023)
Mangrove ecosystems are generally found in all coastal areas of Indonesia, which are affected by tides and inundate these ecosystems along the coast. The function of the mangrove ecosystem as ecotourism is an alternative that can be developed in coastal areas. The purpose of this study was to identify the diversity of flora and fauna, determine the allocation of mangrove ecosystem land for ecotourism and determine the carrying capacity of the mangrove ecosystem area to be used for ecotourism. This research was carried out from January to February 2021 in the Tanjung Lesung area, Banten, with three research stations based on the initial survey and the data provided by the manager. The data taken in this study are mangrove ecosystems, associated biota, mangrove thickness, and respondents from visitors who aim to find out how long it takes their visit. The results obtained are there are nine types of mangroves from six families. The mangrove density of the research location is 796 ind.ha-1. The biota found at the research site found seven biota. The results of the calculation of ecotourism suitability at Station I have a value of 58.3% with the S2 category, and Station II has a value of 72.2% with the S2 category. Station III has a value of 33.3% with the S3 category. The calculation results of the area's carrying capacity for tracking activities are 180 people per day with a usable area of about 2200 m2. Keywords: Carrying Capacity, Ecotourism, Land Suitability, Mangroves, Tanjung Lesung.